Differences attract: An experimental study of focusing in economic choice - Ola Andersson; Jim Ingebretsen Carlson; Erik Wengström (Research Institute of Industrial Economics (IFN), 2016)
Several recent behavioral models of choice build on the idea that decision makers put more weight on attributes in which the available options differ more. We test this assumption in a controlled experiment where such biases will generate choice inconsistencies. As hypothesized, we find that subjects make more inconsistent choices when we add new options that affect the maximal difference in attributes among the options. Our findings suggest that the decision maker's focus is drawn to attributes that stand out. We also test the focusing effect against theories of decoy effects (asymmetric dominance), but we find that the focus effect dominates.
Keywords: D03; D12; C91; 330; Individual decision making; Focus; Attention; Salience; Decoy; Experiments